The Penguin guide to punctuation - Trask, R. L. (Robert Lawrence), 1944-2004. (London : Penguin, 1997)
Effective and easy to follow, this step-by-step guide will dispel the mysteries of punctuation and prove an invaluable aid to writing clear English.
Why learn to punctuate? -- The full stop, the question mark and the exclamation mark -- The comma -- The colon and semicolon -- The apostrophe -- The hyphen and the dash -- Capital letters and abbreviations -- Quotation marks -- Miscellaneous -- Punctuating essays and letters.
P.B
P.B
Keywords: English language -- Punctuation; Langues; Expression écrite; Manuels de stylistique; English language -- Punctuation; Englisch; Zeichensetzung; Interpunctie; Engels; Anglais (langue) -- Ponctuation; Englisch